Single-Nucleotide Polymorphism-Based Genetic Diversity Analysis of Clinical Pseudomonas aeruginosa Isolates. (1st April 2020) - Muthukumarasamy, Uthayakumar; Preusse, Matthias; Kordes, Adrian; Koska, Michal; Schniederjans, Monika; Khaledi, Ariane; Häussler, Susanne
Abstract: Extensive use of next-generation sequencing has the potential to transform our knowledge on how genomic variation within bacterial species impacts phenotypic versatility. Because different environments have unique selection pressures, they drive divergent evolution. However, there is also parallel or convergent evolution of traits in independent bacterial isolates inhabiting similar environments. The application of tools to describe population-wide genomic diversity provides an opportunity to measure the predictability of genetic changes underlying adaptation. Here, we describe patterns of sequence variations in the core genome among 99 individual Pseudomonas aeruginosa clinical isolates and identified single-nucleotide polymorphisms that are the basis for branching of the phylogenetic tree. We also identified single-nucleotide polymorphisms that were acquired independently, in separate lineages, and not through inheritance from a common ancestor. Although our results demonstrate that the Pseudomonas aeruginosa core genome is highly conserved and in general, not subject to adaptive evolution, instances of parallel evolution will provide an opportunity to uncover genetic changes that underlie phenotypic diversity.